THE ORIGINS OF CIVILIZATION IN PERU: THE NORCENTRAL AREA AND THE SUPE VALLEY DURING THE LATE ARCHAIC - Shady Solís, Ruth (2000)
In chis work che authors present the main urban centers identified in che Supe vallcy, bascd on che survcy made by chem among the years 1994 and 1995. They anticipare sorne inferences chat should stiJI be considered as preliminary as long as excavations are not carricd out in ocher sites of the valley outside of Caral, establishment where it is carrying out cxcavations from 1996 and bascd on which chis information has been confronted. In chis article che authors state that during the Late Archaic period, it existed in the Supe valley a group of urban centers, built by a population that was culturally integratcd, in which would have been formed the pristine State, with an unified government